Origem e diferenciação do sistema ZZ/ZW de cromossomos sexuais: análises comparativas entre espécies de répteis e aves - Setti, Príncia Grejo (Universidade Federal de São Carlos, 2025)
Sex chromosomes are highly dynamic structures in vertebrates, showing distinct evolutionary trajectories across lineages. This dissertation investigated the origin and differentiation of the ZZ/ZW system in Palaeognathae birds and Colubridae snakes, focusing on the characterization of satellite DNAs and other repetitive elements. An integrative approach combining classical cytogenetics, in situ hybridization (FISH, CGH), and low-coverage genomic analyses was applied. In birds, sex chromosomes ranged from homomorphic in ratites to highly heteromorphic in Tinamiformes, indicating different stages of differentiation. In Ptyas snakes, W chromosomes showed little morphological divergence from Z, but were enriched in heterochromatin and repetitive sequences, suggesting that heterochromatinization may precede visible heteromorphy. The results demonstrate that sex chromosome evolution does not follow a single pattern but is shaped by multiple historical and ecological factors. This work contributes to the understanding of the evolutionary diversity of ZW systems and highlights the relevance of comparative studies integrating cytogenetics, genomics, and evolutionary biology.
Origin and differentiation of the ZZ/ZW sex chromosome system: comparative analyses among reptile and bird species
Keywords: Cromossomos sexuais; DNA satélite; Heterocromatina; Evolução cromossômica; Sistema ZW; CIENCIAS BIOLOGICAS::GENETICA; 4. Educação de Qualidade